2023
DOI: 10.1002/mco2.205
|View full text |Cite
|
Sign up to set email alerts
|

Cryo‐EM structure of orphan G protein‐coupled receptor GPR21

Abstract: GPR21 belongs to class A orphan G protein‐coupled receptor (GPCR). The endogenous ligands for human GPR21 remain unidentified. GPR21 expression is associated with developing type 2 diabetes (T2DM), a multifactorial metabolic disease caused by pancreatic β‐cell dysfunction, decreasing insulin production, insulin resistance, and obesity. Animal studies suggested that GPR21 is a potential therapeutic target for T2DM treatment. The underlying mechanisms leading to GPR21 self‐activation remain unknown. In our co‐ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Unexpectedly, a disulfide observed between TM6 and TM7, while adjacent to the critical tryptophan rotamer toggle switch, proved not to be critical for GPR61 constitutive activity. The agonist-like motif (ALM) of ECL2 reported for GPR52, GPR21, and GPR12 30 33 to drive constitutive activity also does not appear to be present in GPR61, and we have found no structural evidence of binding to the orthosteric site by N-terminal residues with a reported role in activation 9 . The lack of some key sequence features found in many other receptors, such as an ionic lock or sodium binding site, may suggest less stabilization of the inactive state.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Unexpectedly, a disulfide observed between TM6 and TM7, while adjacent to the critical tryptophan rotamer toggle switch, proved not to be critical for GPR61 constitutive activity. The agonist-like motif (ALM) of ECL2 reported for GPR52, GPR21, and GPR12 30 33 to drive constitutive activity also does not appear to be present in GPR61, and we have found no structural evidence of binding to the orthosteric site by N-terminal residues with a reported role in activation 9 . The lack of some key sequence features found in many other receptors, such as an ionic lock or sodium binding site, may suggest less stabilization of the inactive state.…”
Section: Discussionmentioning
confidence: 54%
“…An agonist-like motif (ALM) found in ECL2 has recently been identified in several receptors, including GPR52, GPR21, and GPR12 30 33 as a stimulator of constitutive receptor activity. To probe the potential role of ECL2 in GPR61 activation, we examined the basal activity of GPR61 with point mutations in ECL2 designed to weaken its interactions with the orthosteric site (Q198A, W199A) and/or abolish the conserved disulfide (Δ195-201(GGSGGSGG), C195A) (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4d ). Recent studies have shown that several class A orphan GPCRs are self-activated by ECL2 that directly penetrates to the orthosteric binding pocket, such as GPR21 22 , GPR52 23 , GPR17 24 , GPR161 and GPR61 25 . Although the ECL2 of GCGR partially overlaps with the peptide-binding site, the majority of which is likely disordered owing to the missing cryo-EM density, suggesting its conformational flexibility and non-built-in agonist nature.…”
Section: Resultsmentioning
confidence: 99%
“…Recently published structures of GPR12 11 in subgroup II and GPR21 9 , 10 and GPR52 8 in subgroup III in complex with G s revealed no ligands bound to the receptors, but instead showed that ECL2 of these receptors penetrate into the orthosteric pocket, leading to a self-activation model. Since no structures of receptors in group I have been reported, we further determined the cryo-EM structures of GPR161‒G s and GPR61‒G s complexes using the same strategy as GPR174 at nominal resolutions of 3.1 and 3.2 Å, respectively (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%